A timed Phalen's test predicts abnormal electrophysiology in carpal tunnel syndrome. Issue 4 (29th January 2021) - Alanazy, Mohammed H.; Albulaihe, Hana; Alhumayyd, Ziad; Albarrak, Anas M.; Abuzinadah, Ahmad R.
Abstract: Objective: Previous studies reported variable sensitivity and specificity of the Phalen test. We investigated whether a timed Phalen's test (TPT) could predict abnormal nerve conduction studies (NCS) results in carpal tunnel syndrome (CTS). Methods: Patients with CTS were consecutively recruited. A neurologist confirmed the clinical diagnosis of CTS and recorded the TPT before NCS were performed. Another neurologist, blinded to the TPT, graded the severity of NCS. The TPT sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: In total, 403 patients with 706 hands were recruited and diagnosed with CTS; 465 hands had positive TPT, and 611 hands showed abnormal NCS results. A positive TPT at ≤ 10 s had a specificity of 96.8% and a PPV of 96.6% in predicting abnormal NCS. The sensitivity and NPV of TPT were insignificant. Discussion: A positive TPT at ≤ 10 s can be useful in predicting NCS abnormalities in patients with CTS. Abstract : The timed Phalen's test can be useful in predicting abnormal NCS that confirms median neuropathy at the wrist in a subgroup of CTS patients.